West Nile Virus Outbreak in Israel 2024 Compared with Previous Seasons: A Retrospective Study - Guy Katzenellenbogen; Michal Canetti; Ili Margalit; Yonatan Shusterman; Alon Simchovitz-Gesher; Lior Naveh; Nadav Baharav; Miki Goldenfeld; Ana Belkin; Marina Brod; Anat Wieder-Finesod; Eyal Leshem; et al. (Infectious Diseases and Therapy)
Abstract Introduction Since May 2024, Israel has been experiencing a large West Nile virus (WNV) outbreak. We aimed to compare the clinical characteristics and outcomes of hospitalized cases to previous years and identify predictors of poor outcomes. Methods A retrospective study. We compared WNV infection cases hospitalized during the 2024 outbreak (from 29 May to 29 July) to cases hospitalized during 2018–2023. For the entire cohort, risk factors for poor outcomes were investigated using multivariable analyses. The primary outcomes were death and a composite outcome of 30-day all-cause mortality, prolonged hospitalization (≥ 28 days), or discharge to an institution. Results We included 134 patients, 103 admitted during 2024 and 31 during 2018–2023. The majority (109/134, 81%) had neuroinvasive disease, mostly encephalitis. In 2024, patients were older, with a lower functional state, and a higher proportion were severely immunocompromised. Mortality was numerically higher in 2024 (15/103, 15% versus 2/31, 6%). Altogether, nearly 40% of patients had poor outcomes, including 13% (17/134) mortality and 25% (34/134) discharged to institutions. Nearly 30% of patients who were severely immunocompromised died; all had B-cell depletion. Age was the only significant predictor of poor outcomes in multivariable analysis; however, patients with B-cell depletion had > 3 times higher odds for mortality (odds ratio 3.26, 95% confidence interval 0.73–13.07). Conclusions The large 2024 outbreak of WNV was associated with considerable mortality and functional impairment among hospitalized patients that was higher compared with previous years. Poor outcomes were particularly observed in older adults and patients with B-cell depletion. The observation of severe disease and poor outcomes in patients with B-cell depletion, as well as possible therapeutic implications, should be further investigated.